CR1 BINDING ASSAY: A NOVEL ELISA ASSAY FOR MEASURING CIRCULATING IMMUNE COMPLEXES - Mibei, Erick K; Rono, Salinah J; Stoute, Jose; Waitumbi, John N (European Scientific Journal, ESJ, 2014)
There are over fifty methods which have been described for the assessment of immune complexes in sera or plasma. The measurement of circulating immune complexes in sera of patients with different diseases has been frequently used for the assessment of disease activity for the purposes of disease management/therapy and control. Complement 1q (C1q) binding assay has been the most widely used. In the present study circulating immune complexes (CIC), were measured for the purposes of assessing the relationship with the severity of Plasmodium falciparum severe malarial anaemia. Three methods were used, with two being C1q-based assays and a novel CR1 binding assay. The ability of the methods to discriminate between the severe malarial anaemia cases and their controls was assessed with reference to a common heat aggregated human IgG standard. The three methods used showed a similar trend in detection of levels of CIC in sera and all methods showed elevated levels of CIC in sera of severe malarial anaemia cases compared to their controls. When the cases were compared to their symptomatic controls, the commercial Quidel C1q kit showed a significance difference between SA and UM of p = 0.04 while C1q in-house assay showed a highly significant difference for the two groups (p = 0.01). CR1 binding assay also showed a significance difference between SA and UM (p = 0.04). When cases were compared to their symptomatic controls, Quidel C1q kit had p = 0.001, C1Q in-house assay had p = 0.006 while CR1 binding assay had p = 0.01. Their level of detection differed and this can be attributed to different tracing principles and the nature or properties of the immune complexes detected. From the results it shows that for the screening of CIC in sera, the use of two or more methods will enable detection of ICs of various sizes and complexities, and the nature of IC should be considered so as to select the most appropriate method that will enable a valid assessment to be carried out.